2021
DOI: 10.18632/aging.202832
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the mechanisms of Modified Xiaoyaosan (tiaogan-liqi prescription) in suppressing the progression of atherosclerosis, by means of integrative pharmacology and experimental validation

Abstract: Atherosclerosis (AS)-related diseases remain among the leading causes of death worldwide. Modified Xiaoyaosan (also called Tiaogan-Liqi prescription, TGLQ), a traditional Chinese medical formulation, has been widely applied in the treatment of AS-related diseases. The aim of this study was to investigate the underlying pharmacological mechanisms of TGLQ in acting on AS. A total of 548 chemical compounds contained in TGLQ, and 969 putative targets, were collected from the Computation Platform for Integrative Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Among them, Zishui Tiaogan Decoction originated from the Zishui Qinggan Decoction of a famous doctor in the Qing Dynasty. e Zishui Tiaogan Decoction was different from the Zishui Qinggan Decoction in that it was mainly used to invigorate the kidney and was supplemented by Qinggan [23]. In addition to Si Miao San, Achyranthes bidentata and Poria cocos were added to make Simiao powder more effective in dehumidifying [24].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Zishui Tiaogan Decoction originated from the Zishui Qinggan Decoction of a famous doctor in the Qing Dynasty. e Zishui Tiaogan Decoction was different from the Zishui Qinggan Decoction in that it was mainly used to invigorate the kidney and was supplemented by Qinggan [23]. In addition to Si Miao San, Achyranthes bidentata and Poria cocos were added to make Simiao powder more effective in dehumidifying [24].…”
Section: Discussionmentioning
confidence: 99%
“…The integrated pharmacological research on the derivative formula of Xiaoyao capsules found that the key targets of Chinese medicine components were significantly related to lipid metabolism and inflammation. In vivo and in vitro experiments confirmed that the capsule significantly reduced plasma inflammatory cytokines, reduced lipid deposition in cells, and inhibited the production of macrophages induced by oxidized low-density lipoproteins [27] . Other studies have shown that the pathological changes in the aortic tissue of rats were delayed, verifying that liver-soothing prescriptions effectively alleviated endothelial injuries [18,20] .…”
Section: Correlation Between the Liver's Function Of Controlling Disp...mentioning
confidence: 74%
“…Specifically, Dendrobine is capable of curtailing inflammatory reactions and oxidative stress via the avenue of FK506-binding protein 1A-associated autophagy ox-LDL in human umbilical vein endothelial cells subjected to Dendrobine treatment ( 115 ). Through ex vivo experiments, Chen M uncovered that Xiaoyaosan effectively hampers the ox-LDL-induced production of inflammatory agents in macrophages ( 116 ).…”
Section: Discussionmentioning
confidence: 99%